Tetrahydrothiophene‐Based Ionic Liquids: Synthesis and Thermodynamic Characterizations - Schmitz, Alexa (ChemistryOpen, 2020)
S‐alkyltetrahydrothiophenium, [C(n)THT](+) bis(trifluorosulfonyl)imide, [NTf(2)](−) room temperature ionic liquids (ILs) and tetraphenylborate, [BPh(4)](−) salts with alkyl chain lengths from C(4) to C(10) have been prepared. The ILs and salts were characterized and their purity verified by (1)H‐ and (13)C‐nuclear magnetic resonance, elemental analysis, ion chromatography, Karl‐Fischer titration, single crystal X‐ray diffraction as well as thermogravimetric analysis. The experimentally determined density and viscosity decrease with increasing temperature. The experimental solubility of the [C(n)THT][NTf(2)]‐ILs in water (75 to 2.2 mg/L for C(4) to C(10)) was modelled with very good agreement by Perturbed Chain Statistical Associating Fluid Theory (PC‐SAFT), based on the extremely low vapor pressures for the [C(n)THT][NTf(2)]‐ILs measured in this work (4.15 to 0.037 ⋅ 10(−7)×p(sat) for C(4) to C(10)). PC‐SAFT is able to predict and correlate different thermodynamic properties by estimating the Helmholtz residual energy.